2019
DOI: 10.1016/j.dadm.2019.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid and plasma neurofilament light relate to abnormal cognition

Abstract: Introduction Neuroaxonal damage may contribute to cognitive changes preceding clinical dementia. Accessible biomarkers are critical for detecting such damage. Methods Plasma and cerebrospinal fluid (CSF) neurofilament light (NFL) were related to neuropsychological performance among Vanderbilt Memory & Aging Project participants (plasma n = 333, 73 ± 7 years; CSF n = 149, 72 ± 6 years) ranging from normal cognition (NC) to mild cognitive impairment (MCI). Models adjusted for age, sex, race/ethnicity, education,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 32 publications
4
60
3
Order By: Relevance
“…On the assumption that elevated NFL reflects white‐matter insult, the absence of an NFL‐cognition relation is in line with demonstrations of weak and non‐significant associations between white matter and cognitive decline in aging 11,21 . Some studies have found that high NFL levels relate to poor cognition, 6,28,29 but observations of stronger correlations of cognition to NFL in individuals with MCI and AD than in controls suggest that a common disease factor could have influenced some previous observations of NFL–cognition relations.…”
Section: Discussionsupporting
confidence: 76%
“…On the assumption that elevated NFL reflects white‐matter insult, the absence of an NFL‐cognition relation is in line with demonstrations of weak and non‐significant associations between white matter and cognitive decline in aging 11,21 . Some studies have found that high NFL levels relate to poor cognition, 6,28,29 but observations of stronger correlations of cognition to NFL in individuals with MCI and AD than in controls suggest that a common disease factor could have influenced some previous observations of NFL–cognition relations.…”
Section: Discussionsupporting
confidence: 76%
“…Emerging evidence indicates that NfL is involved in the pathological mechanism of cognitive declines [ 29 ]. A Chinese Taipei study showed that plasma NfL is a biomarker of cognitive decline in AD and Parkinson's disease (PD), and it is more specific for AD [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it represents a non-specific marker for neuronal damage and has been largely studied in the context of neurodegenerative diseases, including multiple sclerosis (MS), Parkinson’s disease (PD), frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) [ 14 ]. Elevated levels of CSF NfL were found in patients with MCI and AD, associating with the severity of memory impairment as a marker of disease progression [ 15 , 16 , 17 ]. Altogether, studies reported a very good performance of CSF NfL to distinguish AD cases from cognitively healthy controls with no evidence of structural brain damage [ 18 ].…”
Section: Emerging Ad Biomarkers In Biological Fluidsmentioning
confidence: 99%